Measurement of the $Λ_{b}^0$ lifetime in pp collisions at $\sqrt{s} = 7$ TeV - CMS collaboration (2199 authors) (2013)
A measurement of the $\Lambda_b^{0}$ lifetime using the decay $\Lambda_b^{0} \to J/\psi \Lambda$ in proton-proton collisions at $\sqrt{s}$=7 TeV is presented. The data set, corresponding to an integrated luminosity of about 5 inverse femtobarns, was recorded with the CMS experiment at the Large Hadron Collider using triggers that selected dimuon events in the J/$\psi$ mass region. The $\Lambda_b^{0}$ lifetime is measured to be 1.503 +/- 0.052 (stat.) +/- 0.031 (syst.) ps.